ДИЯКОНИ ТА ПСАЛОМЩИКИ В СТРУКТУРІ ЦЕРКОВНОЇ ІЄРАРХІЇ В 20-х рр. ХХ ст. (Zaporizhzhia Historical Review, 2021)
The article analyzes the changes in social and demographic structure of Orthodox church ministers in Ukraine in the 20-s of XX century. The author defines factors, that caused a significant decrease of the number of deacons and psalm-readers. Great attention is paid to the influence of these tendencies on the development of confession life.